Impact of Price Perception, Service Quality, and Brand Image on Customer Satisfaction in Hajj And Umrah Travel Services - Permata, Shynta; Susanto, Heri; Rumna, Rumna (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
This study aims to examine and analyze the Perception of Price, Service Quality, and Brand Image on Customer Satisfaction of Hajj and Umrah Travel. The sample used in this study is Bawazier Travel PT. Sutan Alzahira Wisata. Data were collected using a census method and analyzed using multiple linear regression. Based on this study, it can be concluded that Bawazier Travel customer satisfaction is significantly influenced by price perception, service quality, and brand image. Respondents showed a high level of satisfaction with prices commensurate with benefits, satisfactory service, and Bawazier Travel's reputation as a trusted Umrah travel. Perceptions of reasonable prices, friendly and timely service quality, and a positive brand image also play a major role in increasing customer satisfaction. Therefore, to maintain and increase satisfaction, Bawazier Travel needs to continue to offer competitive prices, maintain service quality, and strengthen its brand image in the eyes of customers.